Influence of extended depth of focus intraocular lenses on visual field sensitivity - Makiko Takahashi; Chiemi Yamashiro; Takuya Yoshimoto; Yuka Kobayashi; Fumiaki Higashijima; Masaaki Kobayashi; Makoto Hatano; Manami Ohta; Tomohiko Nagai; Shinichiro Teranishi; Katsuyoshi Suzuki; Ryu Takabatake; et al. (PLoS ONE, 2020)
Purpose To investigate the influence of EDOF IOLs, TECNIS Symfony® (Johnson & Johnson Surgical Vision, Inc.), on visual field sensitivity and to compare the IOLs with other kinds of IOLs. Methods The subjects included the normal fellow eyes of patients who underwent the Humphrey Field Analyzer (HFA) 30–2 with Swedish Interactive Threshold Algorithm Fast within 6 months after cataract due to glaucoma or suspected glaucoma. Each parameter of HFA was compared among eyes implanted with TENIS Symfony® (EDOF group), diffractive bifocal IOLs (bifocal group), and monofocal IOLs (monofocal group). Results The total of 76 eyes, including 24 eyes in the EDOF group, 26 eyes in the bifocal group, and 26 eyes in the monofocal group, were included in this study. Mean deviation (MD) of HFA was -0.24±0.58 dB in the EDOF group, -1.38±0.58 dB in the bifocal group, and 0.02±0.44 dB in the monofocal group. Foveal threshold (FT) of HFA was 35.8±1.6 dB in the EDOF group, 33.6±1.7 dB in the bifocal group, and 36.6±1.4 dB in the monofocal group. In both MD and FT, there was significant difference between the bifocal group and the others (p<0.001). There was no difference between the EDOF group and the monofocal group. Moreover, there was no significant difference between the three groups about pattern standard deviation (PSD) of HFA. Conclusion TECNIS Symfony® may have little influence on visual field sensitivity, whereas diffractive bifocal IOLs decrease visual field sensitivity.